Does Carbon Emission Disclosure and Environmental Performance Affect the Cost of Debt with Profitability as an Intervening Variable? Evidence from Coal Sub sector Companies Listed on the Indonesia Stock Exchange (2024–2025) - Dede Yusuf Maulana; Aditya Bayu Kusuma; Istikomah Istikomah; Dharnita Chandra; Mardiman Mardiman (Vifada Management and Social Sciences, 2026)
Purpose: This study aims to analyze the effect of carbon emission disclosure and environmental performance on the cost of debt in coal subsector companies listed on the Indonesia Stock Exchange during the 2024–2025 period, with profitability as an intervening variable. This study also seeks to explain whether sustainability disclosure and environmental performance can influence corporate debt financing costs through credit risk perceptions reflected in profitability and cost of debt. Research Design and Methodology: This research uses a quantitative causal-associative approach with panel data. The population consists of coal subsector companies listed on the Indonesia Stock Exchange. The sample was selected using purposive sampling based on several criteria. The index value was calculated by dividing the number of disclosed items by the total disclosure items. Environmental performance was measured using PROPER ratings converted into numerical scores. Profitability was proxied by Return on Assets, calculated by dividing net income by total assets. The cost of debt was measured by dividing interest expense by average interest-bearing debt. Data analysis used panel data regression and mediation testing. Findings and Discussion: The results show that carbon emission disclosure has a significant effect on profitability, while environmental performance does not significantly affect profitability. Carbon emission disclosure, environmental performance, and profitability do not have a significant direct effect on the cost of debt, either partially or simultaneously. The mediation test also shows that profitability does not significantly mediate the relationship between carbon emission disclosure and cost of debt, nor the relationship between environmental performance and cost of debt. These findings indicate that sustainability-related variables in this study have limited explanatory power in determining debt financing costs among coal subsector companies. Implications: The findings imply that carbon emission disclosure can influence internal financial performance, but it has not yet become a decisive factor in creditors’ assessment of debt risk in the coal subsector. Companies should improve the quality, consistency, and credibility of environmental disclosure to strengthen stakeholder trust. Creditors and investors also need to consider broader environmental, financial, and governance indicators in assessing credit risk. Future research should include longer observation periods, additional control variables, and broader ESG indicators to better explain the determinants of cost of debt in emission-intensive industries.